2021
DOI: 10.1111/jnc.15350
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic biomarkers from proteomic characterization of cerebrospinal fluid in patients with brain malignancies

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 67 publications
0
42
0
1
Order By: Relevance
“…Remarkably, we have recently identified CHI3L1 as a key cerebrospinal fluid proteomic biomarker in GB in an independent study (13) . The mRNA level and protein level of CHI3L1 in GB were highly correlated (n = 93, R = 0.85, Supplementary Figure 1A).…”
Section: Figure 1h)mentioning
confidence: 92%
“…Remarkably, we have recently identified CHI3L1 as a key cerebrospinal fluid proteomic biomarker in GB in an independent study (13) . The mRNA level and protein level of CHI3L1 in GB were highly correlated (n = 93, R = 0.85, Supplementary Figure 1A).…”
Section: Figure 1h)mentioning
confidence: 92%
“…Next, we applied a 70% intra-group coverage threshold to obtain a dataset of 755 proteins for downstream analyses, representing an improvement in proteome coverage over the 506 proteins recovered by Schmid and colleagues in a comparable cohort using an identical coverage threshold ( Fig S2A-D ). 16 Tumor suppressor genes (e.g., PTEN, NF1, TP53) and oncogenes (e.g., EGFR, BRAF, PDGFRA) implicated in GBM, BM and CNSL were not reliably recovered by our protocol, which we attributed to our approach preferentially detecting secreted, rather than intracellular or membrane-bound proteins ( Table S1 ). 21 Importantly, UMAP representation of CSF proteomes revealed coherent separation of each diagnostic group, suggesting that CSF proteomics are suitable for diagnosing malignancy, and discriminating between different brain neoplasms ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 95%
“…Functional annotation revealed that malignancy was associated with apoptotic signaling, glycolysis and heme metabolism, whereas non-malignancy was associated with elastic fibres- and extracellular matrix (ECM)-associated proteins, and neuronal and glial processes ( Fig 2C, D ; Fig S3A ). Importantly, using published proteomic CSF data from GBM, 16 BM, 16 CNSL, 16 Alzheimer’s disease (AD), 22 amyotrophic lateral sclerosis (ALS), 23 and clinically-isolated syndrome of demyelination [CIS; first attack of multiple sclerosis (MS)], 24 we demonstrated that our malignancy and non-malignancy signatures are significantly more deregulated in neoplastic disease (GBM, BM, CNSL) than non-neoplastic disease (AD, ALS, CIS/MS) ( Fig 2E, F ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations